The Dynamics of Participation: The Tourism Object Management of Cigaru Blue Lake - Siregar, Herlina; Irfani Lindawati, Yustika (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Changes are also resulted from the community ‘s efforts to develop Cigaru Blue Lake into a tourist attraction. In connection with all the changes that occur by the community participation, this study aims to describe 1) the stage of community participation in the management of Cigaru Blue Lake tourism object, 2) the dynamics of community participation in the management of the tourism object, and 3) the supporting and inhibiting factors of the community participation in the management of Cigaru Blue Lake tourism object. This study uses a qualitative approach with descriptive method. The data are collected through observations, interview, and documentations.  The results of the study show that the dynamics of participation that occurred in Cigaru Blue Lake tourist attraction brought some changes with the addition rides, adequate public facilities, and the ability to collaborate with the local government (Cisoka District). The supporting factors are the programs that are in accordance with the needs and interests of the community and comply with the prevailing values so as to create strong bonds between the communities. Meanwhile, the inhibiting factor is the geographical condition of the region and the week economy state of the community which makes the management run slowly.